Desain Pembelajaran Berbasis Emotional Spiritual Quotient (ESQ) pada Masa Pandemi Covid 19 di Madrasah Ibtidaiyah - Meril Qurniawan (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2020)
ESQ-based learning includes two forms of learning, namely: learning that uses ESQ principles as a basis in the preparation of learning activities, and learning that uses ESQ concepts as part of the content of learning materials that are integrated in the material that has been determined in the content standards or curriculum. Learning based on ESQ principles is designed by combining several learning strategies in one learning process that contains elements of intrapersonal, interpersonal and existential intelligence. ESQ values ​​that are integrated in learning are manifested in self-control when getting a problem or opportunity before responding. These activities include: (1) inviting students to do activities only because of Allah, (2) inviting children to pay attention to others sincerely, helping sincerely, teaching and educating others in need, maintaining attitudes and behavior and follow the Prophet Muhammad SAW. (3) inviting students to always read and deepen the Qur'an and Hadith every day, (4) direct students to have short-term and long-term goals to determine important activities to do, (5) get used to reading prayer before starting the activity and evaluating each activity that has been carried out, (6) inviting students to get used to being orderly and orderly, having clear goals, (7) inviting students to try to achieve their goals.